Study Empiris Kinerja Pemasaran UMKM Donat - Yulianti, Dewi Herlina (BUDGETING : Journal of Business, Management and Accounting, 2023)
This research is a test of "Empirical Study of Donut MSME Marketing Performance in Tanggul District" which has variables influencing market orientation (X1), entrepreneurial orientation (X2), product innovation (X3), and competitive advantage (X4) on marketing performance (Y) Donut UMKM in Tanggul District. This study aims to increase the number of donut MSME actors in Tanggul District, which continues to grow, demanding the ability to compete in marketing their products. This study uses a descriptive research design with a quantitative approach regarding marketing performance characteristics. The research data is based on a review of relevant literature and a questionnaire sent to 42 donut business owners in Tanggul District. Research using saturated sampling method. Methods of data analysis using multiple linear regression. As for the program data using IBM SPSS 25.0 statistics. The results of the study underlined that orientation, entrepreneurial orientation, product innovation, and competitive advantage had a positive and significant effect on the marketing performance of Donut MSMEs in Tanggul District. Keywords: Competitive Advantage; Entrepreneurship Orientation; Market Orientation; Marketing Performance; Product Innovation